2017
DOI: 10.1038/emi.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Antigens Rv0310c and Rv1255c are promising novel biomarkers for the diagnosis ofMycobacterium tuberculosisinfection

Abstract: This study aimed to identify novel immunogenic epitopes from Mycobacterium tuberculosis (MTB) that could be used in tuberculosis (TB) diagnostics. To determine the diagnostic potential of mycobacterial antigens in serodiagnosis of TB, 256 patients were enrolled in a study and divided into two groups: 126 smear-positive pulmonary TB patients (SPPT) and 130 smear-negative pulmonary TB patients (SNPT); 152 bacillus Calmette-Guerin (BCG)-vaccinated healthy people were used as a control. Murine results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Previous studies have reported that the sensitivity and specificity of Rv3872 for detecting LTBI in children were 76% and 80%, respectively, which could elicit a stronger immunoreactivity for discriminating TB from HCs in patients who have received BCG vaccination (Mukherjee et al, 2007;Mahmoudi et al, 2017). In contrast, the remaining antigens (Rv3879, Rv1978, Rv1980c, Rv1981c, Rv3425, and Rv3429) were only tested between patients with TB and HCs with BCG vaccination or LTBI and HCs with BCG vaccination (Mukherjee et al, 2007;Zhang et al, 2007;Chen et al, 2009;Hinks et al, 2009;Wang et al, 2013;Luo et al, 2017;Mahmoudi et al, 2017;Cao et al, 2021). Hinks et al (2009) compared the responses to a range of RD1-encoded antigens (ESAT-6, CFP-10, Rv3879c, Rv3878, Rv3873, and Rv2031c) and defined a similar hierarchy of immunodominance for these antigens in both aTB and LTBI subjects: CFP-10 > ESAT-6 > Rv3879c > Rv3878 > Rv3873 > Rv2031c.…”
Section: Novel Biomarkers Derived From Mycobacterium Tuberculosismentioning
confidence: 99%
“…Previous studies have reported that the sensitivity and specificity of Rv3872 for detecting LTBI in children were 76% and 80%, respectively, which could elicit a stronger immunoreactivity for discriminating TB from HCs in patients who have received BCG vaccination (Mukherjee et al, 2007;Mahmoudi et al, 2017). In contrast, the remaining antigens (Rv3879, Rv1978, Rv1980c, Rv1981c, Rv3425, and Rv3429) were only tested between patients with TB and HCs with BCG vaccination or LTBI and HCs with BCG vaccination (Mukherjee et al, 2007;Zhang et al, 2007;Chen et al, 2009;Hinks et al, 2009;Wang et al, 2013;Luo et al, 2017;Mahmoudi et al, 2017;Cao et al, 2021). Hinks et al (2009) compared the responses to a range of RD1-encoded antigens (ESAT-6, CFP-10, Rv3879c, Rv3878, Rv3873, and Rv2031c) and defined a similar hierarchy of immunodominance for these antigens in both aTB and LTBI subjects: CFP-10 > ESAT-6 > Rv3879c > Rv3878 > Rv3873 > Rv2031c.…”
Section: Novel Biomarkers Derived From Mycobacterium Tuberculosismentioning
confidence: 99%
“…In RDs, some antigens were reported to be potential markers for improving the TB serological diagnosis. ESAT‐6 (Rv3875), Rv3872, CFP‐10 (Rv3874) and Rv3879 in RD1 (Dillon et al ., ; Mukherjee et al ., ; Liu et al ., ), Rv1980c in RD2 (Zhu et al ., ), Rv0222 in RD4 (Rosenkrands et al ., ), Rv0310c in RD8, Rv1255c in RD10 (Luo et al ., ), Rv3425 in RD11 (Zhang et al ., ), and Rv2645 in RD13 (Luo et al ., ) have shown potential as TB diagnostic antigens. The genes in RD1, RD2 and RD8 have been reported to be conserved in both M. tuberculosis and Mycobacterium bovis ( M. bovis ), but are absent in M. bovis BCG, as well as several non‐tuberculosis mycobacteria (NTM), including Mycobacterium avium (Parkash et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The lymphocytes were plated at 2 9 10 6 cells/well in 24-well plates (Costar, Corning, NY, USA) in RPMI-1640 medium containing 10% fetal calf serum. Endotoxin detection (Chinese Horseshoe Crab Reagent Manufactory, Xiamen, China) and removal of these proteins were performed as described previously (Luo et al, 2017). The cells were stimulated with purified recombinant proteins (15 lg ml À1 ) at 37°C for 48 h. After stimulation, the supernatants were collected, and IFN-c was detected using a mouse IFN-c ELISA Kit (Neobioscience).…”
Section: Murine Model: Assessment Of Cellular and Humoral Immunity Inmentioning
confidence: 99%
“…More recently, several highly antigenic MTB antigens have been developed for diagnostics with improved sensitivity and specificity than the classical ESAT-6-and CFP-10-based assays such as RV0310c-E and RV1255c-E. Receiver operating characteristic (ROC) analyses have shown that serum IgG against both RV0310c-E and RV1255c-E antigens has better sensitivity and specificity (AUC = 0.8 and 0.808, respectively) in diagnosing MTB compared to ESAT-6 and CFP-10 (AUC = 0.665 and 0.623, respectively) (Luo et al, 2017). Lopez-Ramos et al (2018) showed that the antibodies against MTB antigen P12037 has a sensitivity and specificity of 92% and 91%, respectively in diagnosing active TB when used in concert with sCD14.…”
Section: Prospects With Detection Of Host Immune Biomarkers In Mtb Inmentioning
confidence: 99%